Characteristics of Foraminifera Distribution in Volcanic Tuff of Parepare Tanamailie Pinrang, South Sulawesi - Husain, Ratna (Riviera Publishing, 2023)
This research was conducted to determine and distribute foraminifera in vertical positions using measured stratigraphy. This research aims to analyze the distribution characteristics of foraminifera in the Parepare Tanmailie Pinrang volcanic tuff, South Sulawesi. This research was conducted in the Tanamailie area in Suppa District, Pinrang Regency, South Sulawesi, where the fine-grained Parepare volcanics are well exposed. The method used in this research is field observation. The results of the research show that the analysis and description of fossils found in the measured stratigraphic landscape determined four sequential biozonations, namely from (1) The composition of the bottom layer in the N13 zonation Sphaeroidinellopsis subdevices - Globigerina Drury, (2) The composition of the lower middle layer in the N14-N15 zonation Globigerina nepenthes - Globorotalia (T.) sickness to Globorotalia (T.) continuous, (3) Upper middle layer arrangement zonation N16-N18 Globorotalia (T.) acostaensis acostaensis - Globorotalia (G.) merotumida to Globorotalia (G.) tumi-da plesiotumida – Sphaerodinellopsis subdevices paenedehiscens, (4) Top layer composition of zonation N18-N19 Globorotalia (G.) tumi-da – Sphaerodinellopsis subdevices paenedehiscens to Sphaeroidinella dehiscent dehiscent - Globoquadrina altispira altispira. Analysis of abundant benthic foraminifera. This tough paleoenvironment is characterized by an abundance of Textularis sp and Nodosaria sp, indicating a shallow marine depositional environment.